Isolation Method and Characterization of Outer Membranes Vesicles of Helicobacter pylori Grown in a Chemically Defined Medium - Melo, Joana; Pinto, Vanessa; Fernandes, Tânia; Malheiro, Ana R.; Osório, Hugo; Figueiredo, Ceu; Leite, Marina (Frontiers in Microbiology, 2021)
Outer membrane vesicles (OMVs) are small vesicles constitutively shed by all Gram-negative bacterium, which have been proposed to play a role in Helicobacter pylori persistence and pathogenesis. The methods currently available for the isolation of H. pylori OMVs are diverse and time-consuming, raising the need for a protocol standardization, which was the main aim of this study. Here, we showed that the chemically defined F12 medium, supplemented with cholesterol, nutritionally supports bacterial growth and maintains H. pylori viability for at least 72 h. Additionally, we developed an abridged protocol for isolation of OMVs from these bacterial cultures, which comprises a low-speed centrifugation, supernatant filtration through a 0.45 µm pore, and two ultracentrifugations for OMVs’ recovery and washing. Using this approach, a good yield of highly pure bona fide OMVs was recovered from cultures of different H. pylori strains and in different periods of bacterial growth, as assessed by nanoparticle tracking analysis, transmission electron microscopy, and proteomic analyses, confirming the reliability of the protocol. Analysis of the proteome of OMVs isolated from H. pylori F12-cholesterol cultures at different time points of bacterial growth revealed differentially expressed proteins, including the vacuolating cytotoxin VacA. In conclusion, this work proposes a time- and cost-efficient protocol for the isolation of H. pylori OMVs from a chemically defined culture medium that is suitable for implementation in research and in the biopharmaceutical field.